207k views
4 votes
3x+3y=12 x-5y=10 3(x-5y=10) Janiah is solving the system using elimination. Her first step is shown (The one in parenthesis) What should be her next step a add the equations B divide the equations C subtract the equations D multiply the equations

User Kylex
by
8.0k points

2 Answers

6 votes

Answer: The answer is c! :))

Explanation:

User Paxdora
by
7.3k points
1 vote
Equation 1) 3x + 3y = 12
Equation 2) x - 5y = 10

First step : 3(x - 5y = 10)

Well, we have to simplify this equation first. *Remember, this is the second equation.

Equation 1) 3x + 3y = 12
Equation 2) 3x - 14y = 30

Well, because both equation 1 & 2 have positive 3x in their equations, we must subtract the equations from one another in order to find the y value.

So, your answer is : C) Subtract the equations.

~Hope I helped!~
User Amber Roxanna
by
7.5k points